Anaplasmataceae: Dichotomous Autophagic Interplay for Infection - Patterson, LaNisha L.; Byerly, Caitlan D.; McBride, Jere W. (Frontiers in Immunology, 2021)
Autophagy is a vital conserved degradative process that maintains cellular homeostasis by recycling or eliminating dysfunctional cellular organelles and proteins. More recently, autophagy has become a well-recognized host defense mechanism against intracellular pathogens through a process known as xenophagy. On the host-microbe battlefield many intracellular bacterial pathogens have developed the ability to subvert xenophagy to establish infection. Obligately intracellular bacterial pathogens of the Anaplasmataceae family have developed a dichotomous strategy to exploit the host autophagic pathway to obtain nutrients while escaping lysosomal destruction for intracellular survival within the host cell. In this review, we have summarized the recent findings of how these master manipulators engage and inhibit autophagy for infection and how future studies to further understand mechanisms used by Anaplasmataceae to exploit autophagy may advance novel antimicrobial therapeutic options.